Life-Cycle Educational Choices: Evidence for Two German Cohorts - Martin Biewen; Madalina Tapalaga (Institute for the Study of Labor (IZA), 2016)
We study life-cycle educational transitions in an education system characterized by early tracking and institutionalized branches of academic and vocational training but with the possibility to revise earlier decisions at later stages. Our model covers all major transitions ranging from preschool education through primary and secondary schooling to different forms of tertiary education and vocational training. We consider the role of previous decisions and background characteristics at each decision node and also study 'indirect' routes through the system. Our results suggest that the option to revise earlier decisions is even more socially selective than the earlier track choices that are revised later. We also model unobserved heterogeneity and document the sorting of individuals along unobserved characteristics across the stages of the system.
Keywords: I2; C5; 330; educational decisions; tracking; life-cycle; vocational training; non-standard transitions